2014
DOI: 10.4323/rjlm.2014.105
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the ossification centre morphology in the left hand-wrist bones for age evaluation

Abstract: Determining the chronological age by assessing only the presence of ossification centres and the degree of epiphyseal union observed in the left hand-wrist X-rays could lead to important chronological age underestimation or overestimation. This article presents 4 such cases, emphasizing the importance of assessing the morphology of hand bone elements in addition to their presence in order to increase the accuracy of the chronological age evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…9 The usefulness of carpal bones in estimation of age has been demonstrated in other settings also. [10][11][12][13][14][15] Srivastav et al 6 carried out radiographic study on pediatric subjects of Rajasthan, India from birth to 12 years of age of both sexes. They observed that Pisiform was the last carpal bone to appear.…”
Section: Discussionmentioning
confidence: 99%
“…9 The usefulness of carpal bones in estimation of age has been demonstrated in other settings also. [10][11][12][13][14][15] Srivastav et al 6 carried out radiographic study on pediatric subjects of Rajasthan, India from birth to 12 years of age of both sexes. They observed that Pisiform was the last carpal bone to appear.…”
Section: Discussionmentioning
confidence: 99%
“…Phthalates showed no negative effects as regards the time to pregnancy [18,23,24]. Moreover, some studies reported an association between some phthalates and a shorter time to pregnancy [24].…”
Section: Phthalatesmentioning
confidence: 91%